Does Chemotherapy Modify the Immune Surveillance of Hematological Malignancies? - Barrett, A John (2008)
Malignant diseases induce immune responses against them which have variable success in controlling progression of disease. A variety of congenital and acquired disorders provide evidence in support of T cell or NK cell immune surveillance mechanisms in human hematological malignancies. Furthermore clinical experience with stem cell transplantation underlines the potential for both T and NK cell mediated anti-leukemia effects. Animal models of tumor surveillance and viral driven lymphoproliferative diseases in man emphasize the dynamic nature of the equilibrium between tumors and the immune system which can lead to tumor escape in individuals with normal immune function. In hematological malignancies the implication of a dynamic immune surveillance model is that chemotherapy may disrupt potentially competent immune surveillance mechanisms leading to disease recurrence following successful tumor bulk reduction by chemotherapy. This possibility deserves further investigation with a view to developing strategies to boost immune function following chemotherapy so as to combine the beneficial effect of chemotherapy with an immune response capable of sustaining remissions.